Augmented Reality and Virtual Battle System for Trading Card Game - Akbar Rahmanda, Fachri; Harditya Wienardi S, M.; Reinaldo, Ferdie; Lina Prasetio, Yen; Wongso, Rini; ., Santy (International Journal of Engineering and Technology, 2019)
In this research, we discuss the fairness in gameplay and technology enhancement for playing trading card game. This research mainly focused in applying augmented reality and virtual battle system while developing a new trading card game. Unity is used for developing the game that is based on extreme programming methodology, and the requirements are gathered by interviews, surveys, and research that have been conducted. By applying the augmented reality and virtual battle system, the game will be more interesting and fairer to be played.
Keywords: Augmented Reality; Virtual Battle System; Trading Card Game